The Capitanian Minimum: A Unique Sr Isotope Beacon of the Latest Paleozoic Seawater - Kani, Tomomi; Isozaki, Yukio (Frontiers in Earth Science, 2021)
The long-term trend in the Paleozoic seawater 87Sr/86Sr was punctuated by a unique episode called the “Capitanian minimum” at the end of the Guadalupian (Permian). This article reviews the nature and timing of this major turning point in seawater Sr isotope composition (87Sr/86Sr, δ88Sr) immediately before the Paleozoic-Mesozoic boundary. The lowest value of seawater 87Sr/86Sr (0.7068) in the Capitanian and the subsequent rapid increase at an unusually high rate likely originated from a significant change in continental flux with highly radiogenic Sr. The assembly of the supercontinent Pangea and its subsequent mantle plume-induced breakup were responsible for the overall secular change throughout the Phanerozoic; nonetheless, short-term fluctuations were superimposed by global climate changes. Regarding the unidirectional decrease in Sr isotope values during the early-middle Permian and the Capitanian minimum, the suppression of continental flux was driven by the assembly of Pangea and by climate change with glaciation. In contrast, the extremely rapid increase in Sr isotope values during the Lopingian-early Triassic was induced by global warming. The unique trend change in seawater Sr isotope signatures across the Guadalupian-Lopingian Boundary (GLB) needs to be explained in relation to the Guadalupian extinction and unusual climate change.